2 - Population et Villes Sénégal : La croissance démogéographique: by Amadou Diop - Amadou Diop, (Africa Development, 1990)
The comparison of the 1976 Senegalese population census and that of 1988 has revealed a population increase of 1,883.834 inhabitants corresponding to a 37.6% global growth. However, the dynamic growth has mostly affected urban centers only. Therefore towns have become an unavoidable reality in the structure of the space of Senegal. Hence, various phenomena of increase and decrease resulted in a reclassification of a few towns. However, the reclassification operated in such a way that the town structuring became more disproportionate resulting in making Dakar, the Capital city, weigh heavily on the system and the lower-level towns shrink. In the process, rural areas suffered a lot because of the huge exodus to towns, mostly to those of the Western part of the country. Therefore, it is urgent to strengthen the regional structuring of the country, mostly that of the Eastern part, by enhancing its socio-economic development.